The Importance of Endolymphatic Administration of Drugs In The Treatment of Persistent Postoperative Peritoniti - Ashurmetov A.M.; Usarov A.M.; Fayziyev Y.N. (Academia Open, 2026)
Persistent postoperative peritonitis remains a major challenge in abdominal surgery due to high rates of septic complications, antimicrobial resistance, and insufficient drug concentrations at the site of inflammation, making optimization of regional drug delivery clinically relevant. This study aims to evaluate the clinical and immunological effectiveness of endolymphatic drug administration in the comprehensive treatment of appendicular peritonitis. A retrospective and comparative clinical study was conducted on 66 patients with appendicular peritonitis treated in surgical departments of Tashkent city clinics, divided into a main group receiving endolymphatic therapy and a control group managed with conventional treatment. Clinical severity scores, biochemical parameters, intoxication indices, and immunological markers were analyzed using non-parametric statistical methods. The results demonstrate that endolymphatic drug administration achieved higher local therapeutic concentrations, significantly improved lymphocyte subpopulations, enhanced humoral immunity indicators, reduced endogenous intoxication, and accelerated recovery compared with standard therapy. Unlike prior studies that focused primarily on systemic antibiotic regimens, this research provides empirical evidence on the immunomodulatory and detoxifying advantages of targeted endolymphatic therapy in postoperative peritonitis. These findings contribute to the theoretical understanding of lymphatic system involvement in inflammatory control and support practical and policy-oriented implications for integrating endolymphatic drug administration into surgical infection management protocols to reduce complications and improve patient outcomes.Keywords : Endolymphatic antibiotic therapy, appendicular peritonitis, immunomodulation, lymphatic drug delivery, surgical sepsis prevention, postoperative complicationsHighlight : Endolymphatic therapy increases total T-lymphocytes 1.41-fold and improves immunoglobulin levels significantly. Neutrophil phagocytic activity rises 1.68-fold in treated patients versus minimal improvement in controls. The intervention normalizes microcirculation and enhances lymph transport into bloodstream effectively.